Pre-service teachersâ changing visions of themselves as reform-oriented teachers - Angie Hodge (Arizona State University, 2010)
Both teacher educators and researchers have been trying to ensure that teacher education programs prepare teachers to take on the role of âreform-orientedâ teachers upon entering the classroom. Pre-service teachersâ visions of themselves as future classroom teachers have been found to influence their teaching. The purpose of this study was to further the discussion and understanding of how pre-service teachers envision themselves as future teachers by examining the experiences of 11 pre-services teachers who taught a course in their content area while completing their undergraduate education. Interviews and survey data show that some of the pre-service teachers from this cohort shifted their visions toward a more reform-oriented stance.